Identity construction on young participants of the otaku culture in Chile - Riquelme, Pedro (Última Década, 2020)
This article presents the findings of a research carried out with young participants of the otaku culture in Chile, aiming at understanding the process and mechanisms which individuals have constructed their own personal and social identities from their participation in the specific interactive scenarios – known as “events” - of this youth culture, along with the material and symbolic consumption occurring in such spaces. In order to do this, a sample of seven events carried out in the regions of Valparaiso and Santiago between 2014 and 2015 was developed. Qualitative data was collected by means of participant observation technique, whereas an analytical technique inspired by the fundamentals of B. Glasser and A. Strauss’ “Grounded Theory’ was also performed. The results were classified into three main areas: 1) identity aspects of young otakus, 2) forms of partnership and 3) the role of otaku identity in their own lives.